PENGARUH PENGUNGKAPAN SUKARELA PADA TANGGUNG JAWAB MANAJEMEN ATAS LAPORAN KEUANGAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014) - Bani, Rasis Ahmad; Haryanto, Haryanto (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2015)
This Study aims to eximine how the effect of voluntary disclosure of management's responsibility for the financial reports for earning management. This study analyzed the effect voluntary disclosure of MRF for accrual earning management and real earning management as measured by discretionary accruals, cash flow from operation, discretionary expenses, and production cost.The population of this research are consist of companies are listed on Indonesian Stock Exchange in the year 2014. The samples in this study were selected using purposive sampling, consisting of 127 manufacturing firms in the year 2014. This study used multiple regression analysis model to examine the effect of voluntary disclosure of management's responsibility for the financial reports for accruals earning management and real earning managements.The result of this study indicate that firms with MRF has no effect with accruals earning management and real earning management. The findings from this study show firms with MRF manipulate their earnings use cash flow from operations (sales manipulation).